Transformations and Translocations of Medieval Literature (Interfaces: A Journal of Medieval European Literatures, 2022)
Issue 9 of Interfaces brings together papers given at the Centre for Medieval Literature's symposium on 'Moving Forms: The Transformations and Translocations of Medieval Literature,' held in Athens in 2019. At the heart of the symposium was the exploration of the ways in which the movement of people and books across space and time were driving forces of medieval European literary and intellectual culture. Building on the practices of both comparative literature and entangled history, the symposium aimed to open up connections between literary cultures often considered to be separate. The articles published here cross the geographies and chronologies of medieval literature as they consider a range of forms, from romance to legal writing and from history-writing to animal fables, in examining texts from Georgia, Egypt, Bohemia, Scandinavia and Western Europe (with extensions across the Atlantic into the Americas). While each paper has something for the specialist, we hope that they collectively encourage reading across the full issue, inviting readers to enter into the expanded, comparative and connected, approach to medieval literatures that the symposium explored.Cover image: Pierpaolo Curti, Bridge, 2014, tecnica mista su tela, 120 x 80 cm – Collezione privata – www.pierpaolocurti.com
Keywords: Europe; Middle Ages; Comparative Literature; Movement of People and Books; Medieval Literature